Investigation of High Molecular weight adiponectin in HIV -Infected patients on antiretroviral therapy - Omar, Feirdoz (Division of Chemical Pathology, 2014)
This project aims to investigate the role of multimeric (high molecular weight) adiponectin in the development of metabolic disease resulting from anti-retroviral therapy. Specifically, the aim is to quantify the circulating levels of both total and high molecular weight (HMW) adiponectin and to establish whether a link exists between HMW adiponectin levels and susceptibility to HIV-induced lipodystrophy. Although total adiponectin levels have been shown to be significantly reduced in patients with HIVinduced lipodystrophy, there is no information on whether HMW adiponectin, which appears to be the most biologically active form of adiponectin, is altered in HAARTinduced lipodystrophy, and whether patients with low levels of the HMW form are more susceptible to lipodystrophy.